Joint Waterpipe and Cigarette Smoking as Key Correlate of History of Depression in Iranian Population: A Cross-Sectional Study - Ibrahim Abdollahpour; Zahra Golestannejad; Yahya Salimi; Saharnaz Nedjat; Isabel Aguilar-Palacioc; Mohammad Ali Mansournia; Maximilian de Courten (SAGE Publishing, 2022)
Research on the association between waterpipe smoking and depression is limited. This study aimed to explore the prevalence and adjusted associated correlates of depression among Iranian adult. We analyzed data from 974 participants of a population-based cross-sectional study enrolling 18-50-year-old residents of Tehran, Iran in 2015. Data on lifetime self-reported history of depression, smoking behaviors, socioeconomic status, self-rated health, physical activity, stressful life events as well as a number of relevant confounders was obtained . Logistic regression models were employed for estimating adjusted odds ratios (ORs) and their 95% confidence intervals (CI). The mean (SD) age of the study sample was 32.55 (8.58) years. Of 974 recruited adults, 52.36% were female. The lifetime prevalence of depression in the general population was 17.0%. In general, 21.77% and 24.79% of participant reported lifetime history of cigarette and waterpipe smoking, respectively. While only cigarette smoking (OR = 1.94, 95% CI: (1.04-3.61) and only waterpipe smoking (OR = 1.65, 95% CI: (.95-2.86) were significantly associated with depression, joint cigarette and waterpipe smoking (OR= 3.76, 95% CI: (1.99-6.08) was the strongest correlate of depression followed by female gender (OR = 3.28, 95% CI: (2.08-5.15) and poor self-rated health (OR = 2.47, 95% CI: (1.73-3.53). The prevalence of self-reported depression in general population of Tehran is considerably higher than its global mean. We reported joint cigarette and waterpipe smoking as a significant correlate with depression in the general population. Future health promotion interventions should highlight the disadvantages of joint cigarette and waterpipe smoking targeting adults and especially females.